Identification of Tyrosyl Oleate as a Novel Olive Oil Lipophenol with Proliferative and Antioxidant Properties in Human Keratinocytes - Cinzia Benincasa; Chiara La Torre; Alessia Fazio; Enzo Perri; Maria Cristina Caroleo; Pierluigi Plastina; Erika Cione (MDPI AG, 2021)
Lipophenols are an emerging subclass of phenolic compounds characterized by the presence of a lipid moiety. Recently, hydroxytyrosyl oleate (HtyOle), a derivative of hydroxytyrosol, has been identified in olive oil and by-products. Furthermore, HtyOle possesses anti-inflammatory, antioxidant, and tissue regenerating properties. In this work, the potential occurrence of tyrosyl oleate (TyOle) in olive oil was investigated based on the hypothesis that its precursors tyrosol and oleic acid, both present in relatively high amount can be coupled together. Moreover, TyOle effects have been investigated in human keratinocytes to verify its proliferative and antioxidant properties. The quantitative determination of TyOle was carried out by the external standard method in liquid chromatography coupled with mass spectrometry (LC/MS), in negative mode using multiple reaction monitoring (MRM). The proliferative properties of TyOle on immortalized human keratinocytes (HaCat) were evaluated by 3-(4,5-dimethylthiasol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Morphological changes were observed by fluorescent staining with phalloidin (for F-actin) or 4,6-diamidino-2-phenylindole (DAPI, for chromatin) dye. The antioxidant activity was assessed at the level of production of mitochondrial reactive oxygen species (ROS) induced with UV exposure. TyOle was identified in all the oil samples investigated. Interestingly, TyOle concentration was higher in defective or low-quality oils than in extra virgin oils. The formation of TyOle likely occurs during the crushing and kneading processes and its concentration is related to the increase of rancidity and of the concentration of free precursors. Herein we show that TyOle induced an increase in the viability of HaCat cells and cytoskeletal remodeling.